Advancements in C–PR2 (R = Alkyl or Aryl) Bond Formation Reactions Involving Palladium - Kukowski, Jonathan E.; Smoliakova, Irina P. (Mini-Reviews in Organic Chemistry, 2019)
This review covers recent approaches to the synthesis of tertiary phosphines through the C– PR2 (R = alkyl or aryl) bond formation reactions using palladium. The methods include Pd-catalyzed additions of HPR2 to double and triple bonds, substitution and dynamic kinetic resolution of diaryl (pseudo) halide compounds, reactions of cyclopalladated complexes with MPR2 (M = Li or K) or HPR2, intramolecular phosphination, and C–P+ bond cleavages. Together these methods allow for the preparation of diversely functionalized achiral or enantiopure tertiary phosphines for use in organo- and transition metal catalysis among other important applications.
Keywords: C–P bond formation